Interpretasi Fiqh Siyasah Pemerintahan Islam Pada Masa Al-Khulafa’ Al-Rasyidin - Shobirin Shobirin; Ahmad Rofiq; Ali Imron (Jurnal Penelitian, 2023)
Abstrak This article is entitled, Interpretation of fiqh Siyasah the Pattern of Islamic Government during the Time of al-Khulafa' al-Rasyidin. The problem that was Whichresearched is related to the process of appointment of caliph at the time of al-Khulafa' al-Rasyidin, the pattern of government during the time of al-Khulafa' al-Rasyidin and the practice of Islamic government during the time of al-Khulafa' al-Rashidun. The type of research in this article is library research. Methodologically, library research is included in the qualitative research category, namely research in the form of documents and records of past events, which can be in the form of writing, drawings, or monumental works from someone regarding the history of Islamic government in the era of al-Khulafa' al-Rasyidin. This research uses two approaches adapted to the problems discussed, namely the analytical and historical approaches. The research results displayed in this article are; at the time of al-Khulafa' al-Rasyidin, there was no standard pattern regarding appointing a caliph or head of state. The pattern of government of al-Khulafa' al-Rasyidun, a government based on deliberation, consistently implemented The mandate of "Baitul Mal," putting the interests of the people first from the importance of ashabiyah and implementing a "democratic" government system. While the practice of Islamic government during the time of al-Khulafa' al-Rasyidun is not merely a political government, but can be said to be a representative of the perfect prophecy, they function to carry out national order, maintain peace, defend the borders of the state, and also they carry out the obligations that have been carried out by the Prophet SAW, during his lifetime, namely as murshid, teacher and educator. AbstrakArtikel ini berjudul, Interpretasi fiqh siyasah corak pemerintahan Islam pada masa al-Khulafa’ al-Rasyidin, permasalah yang diteliti adalah berkaitan dengan proses pengangkatan khalifah pada masa al-Khulafa’ al-Rasyidin, corak pemerintahan pada masa al-Khulafa’ al-Rasyidin dan praktek pemerintahan Islam pada masa al-Khulafa’ al-Rasyidun. Jenis penelitian dalam artikel ini adalah library research (penelitian kepustakaan), secara metodologis library research termasuk  kategori penelitian kualitatif, yaitu penelitian berupa dokumen, catatan peristiwa yang sudah berlalu bisa berbentuk tulisan, gambar, atau karya-karya monumental dari seseorang mengenai sejarah pemerintahan Islam pada masa al-Khulafa’ al-Rasyidin. Penelitian ini  menggunakan dua pendekatan yang disesuaikan dengan permasalahan yang dibahas, yaitu pendekatan analitis dan pendekatan historis. Hasil penelitian yang dipaparkan dalam artikel ini adalah pada masa  al-Khulafa' al-Rasyidin tidak terdapat satu pola yang baku mengenai cara pengangkatan khalifah atau kepala negara. Corak pemerintahan al-Khulafa' al-Rasyidun, pemerintahan yang berdasarkan musyawarah, selalu melaksanakan Amanat “Baitul Mal”, mendahulukan kepentingan umat daripada kepentingan ashabiyah dan  melaksanakan sistem pemerintahan “demokrasi”. Sedangkan praktek pemerintahan Islam pada masa al-Khulafa' al-Rasyidun, tidak semata-mata merupakan  pemerintahan politik, tetapi dapat dikatakan sebagai perwakilan  dari nubuwwah yang sempurna, mereka berfungsi untuk  menjalankan tatanan negara, menjaga keamanan, membela batas-batas negeri, dan  juga mereka  melaksanakan kewajiban-kewajiban yang telah dilaksanakan oleh Rasulullah SAW, pada masa hidupnya, yaitu sebagai mursyid, guru dan pendidik.